THE EFFECT OF ADDITION PUMPKIN (Cucurbita sp) FLOUR IN FEED DIFFERENT DOSAGE TO THE COLOUR BRIGHTNESS OF CLOWN FISH (Chromobotiamacracanthus - Razi Azuri; Rusliadi Rusliadi; Iskandar Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTFish Botia is a freshwater fish that have an attractive body colors. Feeding naturallypumpkin flour feed in artificial feed aimed to improve the color quality of clown fish and how long it takes to improve the color. This research was used experimental method with quantutative approach. Research used CRD (Complete Random Design) which consists of 4 treatments with different concentration includes: P0: Positive control, P1: 10%, P2: 15%, and P3: 20%, with 3 replications in each treatments. Parameter in this research are color quality improvements, length and weight accretion.Observation data were analyzed using analysis of variance (ANAVA) α <0.05. The research result showed that feeding the pumpkin flour in artificial diet affected the color improvement of clown fish but did not affect the length and weight of clown fish. The optimal color improvement of clown fish obtained on the treatment with 15% concentration.Keywords: Clown fish, Pumpkin flour, Color quality